Effects of different oocyte retrieval and in vitro maturation systems on bovine embryo development and quality. Issue 3 (June 2015) - Bernal, Sandra Milena; Heinzmann, Julia; Herrmann, Doris; Timmermann, Bernd; Baulain, Ulrich; Großfeld, Rudolf; Diederich, Mike; Lucas-Hahn, Andrea; Niemann, Heiner
Summary Cyclic adenosine monophosphate (cAMP) modulators have been used to avoid spontaneous oocyte maturation and concomitantly improve oocyte developmental competence. The current work evaluated the effects of the addition of cAMP modulators forskolin, 3-isobutyl-1-methylxanthine (IBMX) and cilostamide during in vitro maturation on the quality and yields of blastocysts. The following experimental groups were evaluated: (i) slicing or (ii) aspiration and maturation in tissue culture medium (TCM)199 for 24 h (TCM24slicing and TCM24aspiration, respectively), (iii) aspiration and maturation in the presence of cAMP modulators for 30 h (cAMP30aspiration) and in vivo-produced blastocysts. In vitro-matured oocytes were fertilized and presumptive zygotes were cultured in vitro to assess embryo development. Cleavage, blastocyst formation, blastocyst cell number, mRNA abundance of selected genes and global methylation profiles were evaluated. Blastocyst rate/zygotes for the TCM24aspiration protocol was improved (32.2 ± 2.1%) compared with TCM24slicing and cAMP30aspiration (23.4 ± 1.2% and 23.3 ± 2.0%, respectively, P<0.05). No statistical differences were found for blastocyst cell numbers. The mRNA expression for the EGR1 gene was down-regulated eight-fold in blastocysts that had been produced in vitro compared with their in vivo counterparts. Gene expression profiles for IGF2R, SLC2A8, COX2, DNMT3B and PCK2 did not differ among experimental groups. Bovine testis satellite I and Bos taurus alpha satellite methylation profiles from cAMP30aspiration protocol-derived blastocysts were similar to patterns that were observed in their in vivo equivalents (P > 0.05), while those from the other groups were significantly elevated. It is concluded that retrieval, collection systems and addition of cAMP modulators can affect oocyte developmental competence, which is reflected not only in blastocyst rates but also in global DNA methylation and gene expression patterns.